O jednome graničnom sporu Lovrana i Mošćenica iz 17. stoljeća - Ivana Eterović (Zbornik Lovranšćine, 2018)
17th-century Border Dispute Between Lovran and Mošćenice. Today, the Cesara inlet is the border area between the Municipality of Lovran and the Municipality of Mošćenička Draga, i.e. between their two border cadastral municipalities: Visoče and Kraj. Thanks to its position, it is also the historical natural geographical boundary between Lovran and Mošćenice communes and parishes. Historical sources from the 18th century provide accounts of the disputes of these two neighbouring municipalities about the demarcation of the fishing area. This paper presents in detail a contemporary reading (transcription and translation) of a 17th-century source text written in Italian that describes a physical conflict that emerged at that border area. The transcript in question is of a document dated January 16, 1646 made by Kastav Notary Public Ioannes Conradus Hauch.